Application of Holographic Technology in Education - Suzanna Suzanna (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
This research examines the benefits of holographic technology so that it can be used in education. The current education system already makes extensive use of computer-based information and communication technology; however, the application of holography technology is still a futuristic (future) concept due to difficulties in implementing technical procedures and software requirements in the application of holography technology. This research discusses technology related to holography and how the practice of holography will be applied in the future, affecting many areas of life, especially the world of education. In this study, researchers also conducted experiments on a group of children aged 3 - 4 years using holography technology with the HolograFX Game as a tool for conducting experiments. From the experimental results, it can be concluded that holograms can be accepted by children and provide them with the opportunity to learn in different ways and methods and provide impressive experiences.